2020
DOI: 10.17707/agricultforest.66.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatial and Seasonal Nitrate Variation of Groundwater in the Irrigated Perimeter (Tadla Plain- Morocco)

Abstract: The Nitric pollution in the groundwater of the Tadla plain increases the risk of degrading the quality of water resources and creates a risk to human health and the environment. This study aims to establish the state of pollution of the groundwater by nitrates in Béni Aamir and Béni Moussa aquifers, to follow its temporal evolution and to map its spatial distribution using Surfer software. To assess the contamination of well water by nitric pollution, 200 samples were collected in four seasonal campaigns betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The bacteriological quality study of groundwater in the Tadla plain (Hafiane et al, 2020) showed that the spatial variation in the concentration of fecal indicator germs may be related to the location of wells, the presence of sources of contamination, the sampling period (wet or dry season), and also to anthropogenic activity.…”
Section: Bacteriological Water Qualitymentioning
confidence: 99%
“…The bacteriological quality study of groundwater in the Tadla plain (Hafiane et al, 2020) showed that the spatial variation in the concentration of fecal indicator germs may be related to the location of wells, the presence of sources of contamination, the sampling period (wet or dry season), and also to anthropogenic activity.…”
Section: Bacteriological Water Qualitymentioning
confidence: 99%
“…The challenge facing the regions of Morocco, especially rural areas, is the protection of the quality of groundwater resources. The water sources of the aquifer in the Al-Hoceima region are known for their low piezometric level and, consequently, for their easy and uncontrolled exploitation [10,11]. Indeed, the lack of drinking water supply in certain rural areas or among certain fragile categories of the population pushes them to use water sources for all purposes, including drinking.…”
Section: Introductionmentioning
confidence: 99%
“…The phytosanitary products contribute, making this region one of the most significant agricultural zones in Morocco with good quality and a large quantity of its crops. The deterioration of the groundwater quality is one of the major environmental outcomes of the modernization of cultivation in this perimeter (Oumenskou et al 2018;Hafiane et al 2020). In response to this situation, several scientific investigations have been carried out on water contamination.…”
Section: Introductionmentioning
confidence: 99%